2020
DOI: 10.1007/s11151-020-09770-2
|View full text |Cite
|
Sign up to set email alerts
|

Services Input Intensity and US Manufacturing Employment Responses to the China Shock

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), created in 1992 and directed by Professor Brigid Laffan, aims to develop inter-disciplinary and comparative research and to promote work on the major issues facing the process of integration and European society.The Centre is home to a large post-doctoral programme and hosts major research programmes and projects, and a range of working groups and ad hoc initiatives. The research agenda is organised around a set of core themes and is continuously evolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The structure and predictions of the model are in line with the services‐specific mechanisms in the papers discussed in the text. Related to that, Bamieh, Fiorini, Hoekman, and Jakubik () discussed similar mechanisms and found that higher services input intensity in US manufacturing sectors attenuate the local employment negative response to increased export pressures from China.…”
mentioning
confidence: 83%
“…The structure and predictions of the model are in line with the services‐specific mechanisms in the papers discussed in the text. Related to that, Bamieh, Fiorini, Hoekman, and Jakubik () discussed similar mechanisms and found that higher services input intensity in US manufacturing sectors attenuate the local employment negative response to increased export pressures from China.…”
mentioning
confidence: 83%
“…14. Indirect support to this argument is offered by Bamieh et al (2020). These authors find that, in the case of US local labor markets, higher services inputs use can be an effective tool to respond to the negative employment effects of increasing import competition from China.…”
Section: Discussionmentioning
confidence: 99%
“…Using Swedish firm level data, Lodefalk (2014) shows that in-house and outsourced services help to increase export intensity measured by the share of merchandise exports in total sales. Finally, a recent paper by Bamieh et al (2017) show that more intensive use of producer services appears to be positively associated with resilience to greater import competition.…”
Section: Literature Reviewmentioning
confidence: 94%